A Beginner's Guide to Surviving a Head-On Collision - Matthews, Sebastian, 1965- (Book collections on Project MUSE., 2017)
In this memoir-in-poems, Sebastian Matthews offers a glimpse into his painful yet transcendental journey of healing a broken body, mending a shattered soul, and the utter zeal of making a layup when you thought that would never again be possible. With honesty and wit, this poetic memoir demonstrates how, chipped piece after chipped piece, Matthews and his family put together their fractured lives after nearly losing them in a head-on collision.